Movement synchrony, social bonding and pro-sociality in ontogeny - Tuncgenc, B (2016)
Human sociality, with its wide scope, early ontogeny and pervasiveness across cultures, is remarkable from an evolutionary perspective. We form bonds with other individuals and live in large social groups. We help, empathise with and share our resources with others, who are unfamiliar and genetically unrelated to us. It has been suggested that interpersonal coordination and rhythmic synchronisation of movements may be one proximate mechanism that enables such widespread human sociality and facilitates cooperation. In the last decade, considerable research has examined the effect of movement synchrony on social bonding and cooperation. However, when this thesis started, there was virtually no experimental study investigating the ontogeny of the movement synchrony-social bonding link, which is proposed to have deep evolutionary roots and important, long-lasting consequences in social life. This thesis aims to investigate the effects of movement synchrony on social bonding and cooperative behaviour across different time points in ontogeny. Three experimental studies were conducted examining infancy, early childhood and middle childhood. Each study explored a different aspect of social bonding and cooperation based on the motor, social and cognitive developments that mark that age group. Study 1a found that at 12 months of age, infants prefer individuals who move in synchrony with them, when the individuals are social entities, but not when they are non-social. Study 1b showed no preferences for synchrony at 9 months in either social or non-social contexts, however. Study 2 revealed that in early childhood, performing synchronous movements actively with a peer facilitates helping behaviour among the children, as well as eye contact and mutual smiling during the interaction. Finally, Study 3 showed that the social bonding effects of movement synchrony applied to inter- group settings and that performing synchronous movements with out-groups increased bonding towards the out-group in middle childhood. This thesis followed an interdisciplinary, integrative and naturalistic approach, where (i) literature from a wide range of disciplines motivated and guided the present research; (ii) links between motor, social and cognitive aspects of development, which are often investigated separately, are formed; and (iii) the experiments were designed in ways that represent the real-life occurrences of the investigated phenomena. The current findings provide the first substantial evidence that movement synchrony facilitates social bonding and cooperation in childhood and thereby provides a foundation for future research.